Influences on stakeholder support for a wildfire early warning system in a UK protected area. (1st October 2016) - Edgeley, Catrin M.; Paveglio, Travis B.
ABSTRACT: Projected increases in wildfire risk and impacts to human populations in the UK have prompted the installation of expanded management approaches such as early warning systems (EWSs). Newer iterations of wildfire EWSs help mitigate risk through rapid detection, often using high-resolution monitoring technology and instantaneous information collection. While existing research suggests that local social context plays an important role in the effective application of EWSs, little is known about factors that contribute to stakeholder support for these technocratic systems and their successful implementation in protected areas. This study examines support for an EWS in Northumberland National Park, UK, using focus groups with a broad range of local stakeholders. We found that diverse stakeholder understandings of wildfire, different perceptions of wildfire risk, and varied identification of values at risk collectively help explain mixed support for the EWS. Mixed support also was an outgrowth of distrust between several stakeholder groups, indicating a need for improved communication regarding wildfire risk management across stakeholder groups. Results suggest that EWSs adopted in multi-use protected areas shared by a range of stakeholder are most likely to be successful when stakeholders have shared understandings of the hazard and opportunities for collective planning to address its risks. We conclude that EWSs are a viable approach to wildfire risk reduction, but there needs to be a critical consideration of pre-existing stakeholder dynamics for effective EWS implementation.